2020
DOI: 10.1038/s41598-020-70743-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of immune checkpoint inhibitor-related interstitial lung disease in patients with lung cancer: a single-institution retrospective study

Abstract: Immune checkpoint inhibitors (ICIs) elicit antitumour effects by activating the host immunity and cause immune-related adverse events (irAes). ici-related interstitial lung disease (ici-iLD) is a fatal irAE that is difficult to treat; moreover, its incidence is relatively higher in patients with lung cancer. therefore, early ici-iLD detection and intervention are important for patient safety. However, a risk assessment method for ici-iLD has not been established and the prediction of ici-iLD occurrence is diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 35 publications
2
46
0
Order By: Relevance
“…In the sensitivity analyses excluding the crude ORs, 10 studies were included [25][26][27][28][29][30][31][32][33][34]. Risk factors that could be pooled and were significantly related with the development of irAEs were squamous histology (OR 1.847; CI 95% 1.048-3.256), a higher number of pack-years of smoked tobacco (OR 2.662; CI 95% 1.014-6.989) and the presence of ground glass attenuation in CT imaging (OR 77.1; CI 95% 7.82-760.3) (Supplementary Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…In the sensitivity analyses excluding the crude ORs, 10 studies were included [25][26][27][28][29][30][31][32][33][34]. Risk factors that could be pooled and were significantly related with the development of irAEs were squamous histology (OR 1.847; CI 95% 1.048-3.256), a higher number of pack-years of smoked tobacco (OR 2.662; CI 95% 1.014-6.989) and the presence of ground glass attenuation in CT imaging (OR 77.1; CI 95% 7.82-760.3) (Supplementary Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we collected a set of continuous and categorical predictors of OS reported in the existing literature. The continuous features were age at diagnosis [38], body mass index (BMI) [39], and smoking pack per year [40]. The categorical features were race [41], gender [38], and Eastern Cooperative Oncology Group (ECOG) performance status at diagnosis [42].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…A number of retrospective studies have demonstrated that pre-existing interstitial lung disease (ILD) increases risk of immunemediated pneumonitis in patients receiving ICI (55)(56)(57). A single-center series of 102 patients also showed a trend towards increased risk of ICI-associated pneumonitis in patients with pre-existing chronic obstructive pulmonary disease (COPD) (58). This observation may reflect the inflammatory nature of COPD, which features increased CD8 T-cell numbers and PD-L1 expression (59).…”
Section: Pulmonarymentioning
confidence: 99%